2021
DOI: 10.1083/jcb.202107103
|View full text |Cite
|
Sign up to set email alerts
|

EGFR-RAS-MAPK signaling is confined to the plasma membrane and associated endorecycling protrusions

Abstract: The subcellular localization of RAS GTPases defines the operational compartment of the EGFR-ERK1/2 signaling pathway within cells. Hence, we used live-cell imaging to demonstrate that endogenous KRAS and NRAS tagged with mNeonGreen are predominantly localized to the plasma membrane. NRAS was also present in the Golgi apparatus and a tubular, plasma-membrane derived endorecycling compartment, enriched in recycling endosome markers (TERC). In EGF-stimulated cells, there was essentially no colocalization of eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 58 publications
(101 reference statements)
1
14
0
Order By: Relevance
“…Moreover, unlike ligand-dependent EGFR phosphorylation, p38-dependent EGFR phosphorylation did not trigger downstream signaling responses through ERK1/2. p38-dependent EGFR phosphorylation is associated with clathrin-mediated EGFR endocytosis ( 28 , 79 81 ), and the endocytosed receptor does not contribute to ERK1/2 signaling ( 82 ), suggesting therefore that p38 inhibition may retain EGFR on the plasma membrane where it can more effectively contribute to ERK1/2 signaling during candidalysin stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, unlike ligand-dependent EGFR phosphorylation, p38-dependent EGFR phosphorylation did not trigger downstream signaling responses through ERK1/2. p38-dependent EGFR phosphorylation is associated with clathrin-mediated EGFR endocytosis ( 28 , 79 81 ), and the endocytosed receptor does not contribute to ERK1/2 signaling ( 82 ), suggesting therefore that p38 inhibition may retain EGFR on the plasma membrane where it can more effectively contribute to ERK1/2 signaling during candidalysin stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, we only observed a modest transient increase in ERK activation in retromer-depleted cells. Furthermore, recent studies also suggest that a small population of cell surface EGFR, rather than endosomal EGFR, is responsible for ERK activation [ 49 ]. Therefore, the contributions of endosomal EGFRs in retromer- and SNXs-depleted cells to EGFR signaling need to be fully characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Such an understanding may help generate new hypotheses to explain apparently contradictory observations. For example, recent work from the Sorkin Lab has shown that RAS activation and ERK phosphorylation paradoxically remain dependent on EGFR activity after EGFR and RAS have become physically separated during endocytosis of the receptor (34,36,47).…”
Section: Discussionmentioning
confidence: 99%
“…This new understanding may help explain prior apparently contradictory observations. For example, recent work demonstrates that RAS activity and ERK phosphorylation paradoxically remain dependent on EGFR activity even after EGFR and RAS become physically separated due to EGFR endocytosis and membrane retention of RAS ( 40, 45, 52 ). Based on our work, GAB1-SHP2 complexes, generated by active endocytosed EGFR, may diffuse back to the cell membrane and thereby promote RAS activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation